Adinugraha's Thought Contribution to the Development of Halal Tourism in Indonesia - Hidayatul Sibyani, Hidayatul Sibyani; Wachid Wahyu Adiwinarto (Media Wisata, 2023)
The trend of the Halal Lifestyle has spread globally which then also appears Halal Tourism in countries, especially countries with a majority Muslim population, such as Indonesia. Many countries (both Muslim and non-Muslim countries) have begun to provide tourism products, facilities, and infrastructure to meet the needs of Muslim tourists. The purpose of this study is to determine how Indonesian intellectual thought contributes to the development of Halal Tourism in Indonesia. This research is qualitative research with a taxonomic approach model. The results of this study indicate the contribution of Adinugraha's thoughts regarding the development of the halal tourism sector, especially halal tourism villages that are spreading in Indonesia. Adinugraha's thoughts talk a lot about halal management in Indonesia in several sectors, one of which is halal tourism. The contribution of his thoughts regarding halal tourism is more towards halal tourism villages or raising the themes of halal tourism with local wisdom that exists in Indonesia. The urgency of the human resource aspect as a tourist or host becomes very relevant to support the success of a regional management tourist destination.